Body mass index and its relationship to mental disorders in the Mexican Adolescent Mental Health Survey Índice de masa corporal y su relación con los trastornos mentales en la Encuesta de Salud Mental en Adolescentes de México - Guilherme Borges; Corina Benjet; Maria Elena Medina-Mora; Matthew Miller (Instituto Nacional de Salud Pública, 2010)
OBJECTIVE: To assess the association between body mass index (BMI) and the prevalence of psychiatric disorders among Mexico City adolescents. MATERIAL AND METHODS: Household survey of 3005 adolescents aged 12 to 17 residing in Mexico City in 2005 (response rate = 71%). Face to face interviews were carried out in the homes of participants with informed consent from a parent and/or legal guardian and the assent of the adolescent was obtained. Logistic regression analyses were performed. RESULTS: We only found an association between extremely low BMI and impulse control disorders. Elevated BMI was associated with impulse control disorders only among females. Specific impulse control disorders associated with low BMI included intermittent explosive disorder and conduct disorder. Only intermittent explosive disorder was associated with elevated BMI. CONCLUSION: Among Mexican adolescents, those with extremely high or extremely low BMI were more likely to have impulse control disorders than were adolescents with normal BMI. OBJETIVO: Evaluar la asociación entre el índice de masa corporal (IMC) y la prevalencia de trastornos psiquiátricos en adolescentes de la Ciudad de México. MATERIAL Y MÉTODOS: 3005 adolescentes entre 12 y 17 años fueron entrevistados en 2005 (tasa de respuesta =71%). Las entrevistas cara a cara se hicieron en los hogares de los participantes seleccionados después del consentimiento de los padres o tutores. Se utilizó regresión logística. RESULTADOS: Sólo se encontró asociación entre IMC extremadamente bajo y trastornos de control de impulsos. El IMC elevado estuvo asociado con trastornos de control de impulsos sólo en las mujeres. Los trastornos de control de impulsos específicamente relacionados con bajo IMC incluyen el trastorno explosivo intermitente y el trastorno de conducta. El alto IMC estuvo relacionado únicamente con el trastorno explosivo intermitente. CONCLUSIÓN: Entre los adolescentes mexicanos, es más probable que aquellos con IMC extremadamente alto o bajo presenten trastornos de control de impulsos que aquellos con IMC normal.